Contemporary Approaches to the Treatment of Gastroesophageal Reflux Disease - Boris D. Starostin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2019)
Aim: to describe existing approaches to the treatment of gastroesophageal reflux disease (GERD) in accordance with the requirements of evidence-based medicine, as well as to discuss controversial issues in the management of GERD patients.Key findings. Nonmedical GERD treatment should be based on the reduction of body weight by decreasing the calorie intake and its proper distribution throughout the day, as well as by increasing the level of physical activity. Proton-pump inhibitors (PPIs) are used as the main class of drugs for reflux esophagitis and non-erosive reflux disease (NERD), as well as in cases when the disease is characterized by certain specific features (e.g., the presence of night symptoms) and extraesophageal manifestations. The efficacy of PPI treatment may depend on the genetic polymorphism of the CYP2C19 cytochrome. Rabeprazole is characterized by a predominantly non-enzymatic pathway, providing a more stable pharmacokinetics profile, which is less dependent on the CYP2C19 polymorphism. The duration of the initial and maintenance PPI course is determined by the GERD form. Long-term PPI maintenance therapy is indicated for erosive esophagitis. In the presence of Barrett’s esophagus, this measure is considered from the standpoint of cancer prevention.Conclusion. The use of PPIs is considered to be the key approach in the drug treatment of GERD. The choice of a PPI is based on factors that determine the efficacy and safety of such drugs, namely the rate of the onset of acid suppressive effects, the intensity of acid suppressive effects, the time of the onset of GERD clinical remission, the dependence on the CYP2C19 genetic polymorphism, the absence of significant interaction with other drugs, as well as the presence of pleiotropic effects.